Energy and environmental benefits and policy implications for private passenger vehicles in an emerging metropolis of Southeast Asia – A case study of Metro Manila - Rith, Monorom (Animo Repository, 2020)
An increase in private vehicle fleet and usage exacerbates the overuse of petroleum products, air quality degradation, and public health risks, among other drawbacks. This study investigated the energy and environmental benefits for private passenger vehicles under various scenarios in Metro Manila, the Philippines. The findings are informative to design policy implications for energy and environmental benefits. The study applied the Gaussian copula-based multinomial logit (MNL)-linear regression to develop the household vehicle ownership and energy consumption model using the disaggregated data of 1,795 households collected in 2017. The simulated vehicle fleet and energy consumption were then adopted to extrapolate energy demand, emissions, and public health risks for a 2010–2050 horizon using the bottom-up approach. Under the baseline scenario, the energy demand and carbon dioxide (CO2) emissions will reach 5.45 million tonnes of oil equivalent (Mtoe) and 16.93 million tonnes (Mt) in 2050, respectively. The amounts of hydrocarbon (HC), carbon monoxide (CO), sulfur dioxide (SO2), nitrogen oxides (NOX), particulate matter 10 (PM10) and particulate matter 2.5 (PM2.5) emissions, and economic loss of health risks will be 6,214 tonnes (t), 62,136 t, 536 t, 10,550 t, 1,348 t, 996 t, and 237 Million USD, respectively, under the baseline scenario in 2050. Improvement of accessibility significantly reduces energy demand and CO2 emissions. Introduction of Euro 6 cars and Euro 4 buses and Public Utility Jeepneys noticeably improves public health. The new tax schedules on gas and vehicle maximize the tax revenue. The integration of all the mentioned alternatives can achieve sustainable mobility and urbanization. © 2020 Elsevier Ltd